Digital Project-Based Learning in English Language Education: Instrument for Achieving Sustainable Development Goals - Angel Sophia Intan; Nidya Fitri; Yulia Wiji Astika; Teta Wismar (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Digital Project-Based Learning (DPBL) represents an innovative pedagogical approach that integrates digital technologies within project-based learning to enhance English language education in alignment with the Sustainable Development Goals (SDGs), particularly Goal 4: inclusive and equitable quality education. This study employs a Systematic Literature Review (SLR) to investigate the implementation of DPBL in English language teaching and its effectiveness in fostering essential 21st-century competencies such as communication, digital literacy, critical thinking, and global citizenship. Data were collected from peer-reviewed publications between 2019 and 2024 using the Publish or Perish software and databases including Scopus and Google Scholar. The review highlights that DPBL not only improves English language proficiency but also enhances student motivation, engagement, and awareness of real-world challenges aligned with sustainability values. The findings suggest that DPBL is a promising instructional strategy that bridges language acquisition with global education goals, making it a valuable contribution to both academic and sustainable development agendas.